2017
DOI: 10.1016/j.resuscitation.2017.06.002
|View full text |Cite
|
Sign up to set email alerts
|

‘ Tell me exactly what’s happened ’: When linguistic choices affect the efficiency of emergency calls for cardiac arrest

Abstract: These results suggest that linguistic variations in the way the scripted sentences of a protocol are delivered can have an impact on the efficiency with which call-takers process emergency calls. A better understanding of interactional dynamics between caller and call-taker may translate into improvements of dispatch performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 25 publications
0
22
0
4
Order By: Relevance
“…Sociolinguistic research has shown that even subtle variations in phrasing, word choices and intonation can have significant impacts on the effectiveness of communication in emergency telephone calls (eg, refs 13–16 ). Recent research has explored the impact of call-takers’ linguistic choices on the efficiency of ambulance dispatch in high-acuity cases, including cardiac arrests, 17 and in the detection of agonal breathing. 18 Earlier work has long recognised the communication challenges posed by the pressure of these ‘high-acuity’ and ‘high-stakes’ situations, 19 and on-going research confirms the importance of a more detailed understanding of the dynamics between caller and call-taker to improve dispatch efficiency in these circumstances (eg, refs 17 20 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sociolinguistic research has shown that even subtle variations in phrasing, word choices and intonation can have significant impacts on the effectiveness of communication in emergency telephone calls (eg, refs 13–16 ). Recent research has explored the impact of call-takers’ linguistic choices on the efficiency of ambulance dispatch in high-acuity cases, including cardiac arrests, 17 and in the detection of agonal breathing. 18 Earlier work has long recognised the communication challenges posed by the pressure of these ‘high-acuity’ and ‘high-stakes’ situations, 19 and on-going research confirms the importance of a more detailed understanding of the dynamics between caller and call-taker to improve dispatch efficiency in these circumstances (eg, refs 17 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has explored the impact of call-takers’ linguistic choices on the efficiency of ambulance dispatch in high-acuity cases, including cardiac arrests, 17 and in the detection of agonal breathing. 18 Earlier work has long recognised the communication challenges posed by the pressure of these ‘high-acuity’ and ‘high-stakes’ situations, 19 and on-going research confirms the importance of a more detailed understanding of the dynamics between caller and call-taker to improve dispatch efficiency in these circumstances (eg, refs 17 20 ). However, little work has been undertaken to explore emergency call interactions in lower-acuity situations, such as for ‘primary care sensitive’ problems.…”
Section: Introductionmentioning
confidence: 99%
“…Emergency situations are filled with emotion and navigating the emotions appropriately could lead to a better relay in communication. Clear communication between the caller and call-taker plays a fundamental role in patient outcomes as it allows for the initiation of life-saving bystander interventions while EMS are on their way [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…et effectuer certaines actions (exemple : réanimation cardio-pulmonaire), il est primordial de mieux comprendre les facteurs langagiers et communicationnels qui influencent la compréhension, les réponses, et les actions de l'appelant. Des travaux récents suggèrent que le choix des mots prononcés par le régulateur a un impact sur l'efficacité de la description que l'appelant fait de la situation [4], et sur son consentement à effectuer une réanimation cardiopulmonaire sur le patient [5]. Ce champ d'investigation immense commence à être exploré dans un contexte anglophone [6,7], mais tout reste à faire dans un contexte francophone [8].…”
Section: Linguistique Et Régulation Médicaleunclassified